Analisis Kualitas Layanan E-Commerce Shopee Menggunakan Metode E-Servqual dan Kano - Siti Zainah; Muhammad Luthfi Hamzah; Nesdi Evrilyan Rozanda; Febi Nur Salisah (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2023)
Shopee is one of the most frequently visited online buying and selling sites and has a high number of downloads on the play store. However, in the last two years, Shopee has experienced a decrease in the average number of monthly visitors. The purpose of this research is to understand the quality of service provided by Shopee on its website or application. The E-Servqual method is used to measure the gap between attributes and customer service expectations and the Kano model is used to classify attributes and determine the extent to which service attributes meet customer satisfaction. The results of calculations using the E-Servqual method show that the quality of services provided has not met customer expectations, because all attributes have negative gap values. And the results of calculations using the Kano model identify 11 attributes that must be prioritized, due to a linear relationship between attribute performance and customer satisfaction, 11 attributes that need to be maintained, because an increase in attribute performance will result in a very high level of satisfaction and five attributes that need to be improved in order to maximize satisfaction towards customers. Keywords— Service Quality, Customer Satisfaction, Shopee E-Commerce, E-Servqual, Canoe